Management of acute central retinal artery occlusion: Intravenous thrombolysis is feasible and safe. Issue 7 (October 2017) - Préterre, Cécile; Godeneche, Gaelle; Vandamme, Xavier; Ronzière, Thomas; Lamy, Matthias; Breuilly, Christophe; Urbanczyk, Cédric; Wolff, Valérie; Lebranchu, Pierre; Sevin-Allouet, Mathieu; Guillon, Benoit
Background: Although acute central retinal artery occlusion is as a stroke in the carotid territory (retinal artery), its management remains controversial. The aim of this study was to assess the feasibility and safety of intravenous thrombolysis delivered within 6 h of central retinal artery occlusion in French stroke units. Methods: We performed a retrospective analysis of patients treated with intravenous alteplase (recombinant tissue-plasminogen activator), based on stroke units thrombolysis registers from June 2005 to June 2015, and we selected those who had acute central retinal artery occlusion. The feasibility was assessed by the ratio of patients that had received intravenous alteplase within 6 h after central retinal artery occlusion onset among those who had been admitted to the same hospital for acute central retinal artery occlusion. All adverse events were documented. Results: Thirty patients were included. Visual acuity before treatment was limited to "hand motion", or worse, in 90% of the cases. The mean onset-to-needle time was 273 min. The individuals treated with intravenous alteplase for central retinal artery occlusion represented 10.2% of all of the patients hospitalized for central retinal artery occlusion in 2013 and 2014. We observed one occurrence of major bleeding, a symptomatic intracerebral hemorrhage. Conclusion: When applied early on, intravenous thrombolysis appears to be feasible and safe, provided that contraindications are given due consideration. Whether intravenous thrombolysis is more effective than conservative therapy remains to be determined. In order to conduct a well-designed prospective randomized control trial, an organized network should be in place.